Immersive virtual reality as a teaching tool for neuroanatomy. Issue 10 (18th July 2017) - Stepan, Katelyn; Zeiger, Joshua; Hanchuk, Stephanie; Del Signore, Anthony; Shrivastava, Raj; Govindaraj, Satish; Iloreta, Alfred
Abstract : Background: Three‐dimensional (3D) computer modeling and interactive virtual reality (VR) simulation are validated teaching techniques used throughout medical disciplines. Little objective data exists supporting its use in teaching clinical anatomy. Learner motivation is thought to limit the rate of utilization of such novel technologies. The purpose of this study is to evaluate the effectiveness, satisfaction, and motivation associated with immersive VR simulation in teaching medical students neuroanatomy. Methods: Images of normal cerebral anatomy were reconstructed from human Digital Imaging and Communications in Medicine (DICOM) computed tomography (CT) imaging and magnetic resonance imaging (MRI) into 3D VR formats compatible with the Oculus Rift VR System, a head‐mounted display with tracking capabilities allowing for an immersive VR experience. The ventricular system and cerebral vasculature were highlighted and labeled to create a focused interactive model. We conducted a randomized controlled study with 66 medical students (33 in both the control and experimental groups). Pertinent neuroanatomical structures were studied using either online textbooks or the VR interactive model, respectively. We then evaluated the students' anatomy knowledge, educational experience, and motivation (using the Instructional Materials Motivation Survey [IMMS], a previously validated assessment). Results: There was no significant difference in anatomy knowledge between the 2 groups on preintervention, postintervention, or retention quizzes. The VR group found the learning experience to be significantly more engaging, enjoyable, and useful (all p < 0.01) and scored significantly higher on the motivation assessment ( p < 0.01). Conclusion: Immersive VR educational tools awarded a more positive learner experience and enhanced student motivation. However, the technology was equally as effective as the traditional text books in teaching neuroanatomy.